(untitled) (Bioscience Journal, 2019)
This study was designed to assess the effects of different types of organic matter on the quality and biochemical properties of red seedless watermelon. The research was a single factor experiment, which involved six (6) treatments and four (4) replications. Watermelon grown and harvested from five (5) different organic matter sources, namely; vermicompost (VC), poultry manure (PM), cow dung (CD), goat dung (GD), and moringa leaf extract (MLE), at the rates of 10 ton, 20 ton, 30 ton, 30 ton, and 3000 L ha-1, respectively, were used in this study. The results revealed that the treatment of vermicompost improved the chlorophyll content, chlorophyll fluorescence, stomatal conductance, internal carbon dioxide, net photosynthetic rate, fruit weight and mineral nutrient content of watermelon. The application of cow dung reduced the rind thickness and increased the TSS and antioxidant activity of the watermelon. The goat dung treatment significantly affected fruit size, juice content and the pH content of the watermelon’s fruit juice. The poultry manure (PM) and moringa extract (MLE) treatments resulted in the highest anthocyanin content of all the watermelon. Although all the organic matter, in their unique ways, improved the quality of red seedless watermelon, the study shows that the vermicompost application had better growth, yield and improvement in the quality of watermelon.